Echocardiographic Evaluation of Left Atrial Function to Discriminate Non-Valvular Atrial Fibrillation Development in Patients with Apical Hypertrophic Cardiomyopathy - Kao, Yu-Cheng (Acta Cardiol Sin, 2020)
BACKGROUND: Data is limited on baseline left atrial (LA) myocardial mechanics between apical hypertrophic cardiomyopathy (ApHCM) patients who develop non-valvular atrial fibrillation (NVAF) during follow-up and those who do not. METHODS: This retrospective study investigated the clinical outcomes of consecutive patients newly diagnosed with ApHCM between August 2011 and July 2014 who were followed-up for at least 3 years. The patients underwent 12-lead surface electrocardiography and/or 24-hour Holter electrocardiography at least once a year. The patients were divided into two groups, namely those who did or did not exhibit NVAF during follow-up, respectively. The baseline clinical and echocardiographic data of the two groups were compared. RESULTS: Twenty patients were studied, five of whom were lost to follow-up. Of the remaining 15 ApHCM patients, seven developed NVAF. No differences were observed in the clinical characteristics of the two groups. However, for the echocardiographic data, the NVAF development group exhibited a larger LA volume and impaired LA reservoir, conduit and booster functions. The NVAF development group also showed lower peak LA strain and stiffer left atrium. The LA volume, function, global strain and stiffness were all statistically associated with NVAF development. Among these parameters, a LA conduit function of ≤ 24.9% was found to be the best parameter to discriminate NVAF development. CONCLUSIONS: The baseline LA function was impaired in the ApHCM patients who subsequently developed NVAF during follow-up. A LA conduit function of ≤ 24.9% was strongly associated with NVAF development.